X-ray radiography of the overheating instability in underwater electrical explosions of wires - Yanuka,D; Rososhek,A; Theocharous,S; Bland,SN; Krasik,YE; Olbinado,MP; Rack,A; Oreshkin,EV (Physics of Plasmas, 2019)
We present the measurements of the development of striation like instabilities during the electrical driven explosions of wires in a waterbath. In vacuum based wire explosion experiments, such instabilities have long been known. However, in spite of intense research into theexplosion of wires in liquids, the development of these instabilities has either not been observed or has been assumed to play a minor role inthe parameters of the exploding wire due to the tamping of the wire’s explosion. Using synchrotron based multiframe radiography, we haveseen the development of platelike density structures along an exploding copper wire. Our measurements were compared to a 2Dmagnetohydrodynamics simulation, showing similar striation formation. These observed instabilities could affect the measurements of theconductivity of the wire material in the gas-plasma state—an important parameter in the warm dense matter community. The striationscould also act as a seed for other instabilities later in time if the wire is in a dense flow of material or experiences a shock from an adjacentwire—as it would do in experiments with arrays of wires.